Dental Restoration Longevity among Geriatric and Special Needs Patients. (January 2019) - Caplan, D.J.; Li, Y.; Wang, W.; Kang, S.; Marchini, L.; Cowen, H.J.; Yan, J.
Introduction: Although the population is aging and retaining more teeth, there is a lack of studies that address the longevity of dental restorations placed among older adults. Objectives: This study aimed to describe the survival trajectory of dental restorations placed in an outpatient population of geriatric and adult special needs patients over a 15-y span, with particular interest in the longevity of subsequent restorations in teeth that received multiple restorations over time. Methods: Dental restorations of different types and sizes in patients aged ≥65 y treated between 2000 and 2014 at the University of Iowa College of Dentistry were followed until they incurred an event (i.e., restoration replacement, extraction of the tooth, or endodontic treatment of the tooth). Survival analysis and extended Cox regression models were used to generate hazard ratios for selected predictor variables. Results and Conclusion: A total of 9, 184 restorations were followed among 1, 551 unique patients. During the follow-up period, 28.7% of these restorations incurred an event, and overall the restorations had a median life span of 6.2 y. In multivariable regression models, after controlling for sex and age, a greater number of restoration surfaces were associated with higher risks of failure, and the initial restoration recorded in the database for each participant tended to have a lower risk of failure than that of restorations that included any of those same surfaces that were placed later. This information could be helpful to older adult patients considering various restorative treatment options during the dental treatment–planning and informed consent process. Knowledge Transfer Statement: Informed decision making with regard to potential treatment options is an important component of health and well-being. The present study could contribute to the improved health of older adult dental patients by providing baseline information that clinicians can use as they discuss different restorative treatment options with these patients and their caregivers during the informed consent process.